Study of geomorphological changes - natural and human - for the period (2007-2025) using Geographic Information Systems (GIS): A case study of Wadi Hamad Al-Tajat Basin) - Dr.. Lazim Muhammed Mahmood Al-Jubouri; Ast. Lecturer. Mahmood Ibrahim Khalaf (Journal of College of Education, 2026)
This research focuses on analyzing the geomorphological changes that have occurred in the Hamad Al-Tajat Valley basin using Geographic Information Systems (GIS) and remote sensing techniques. The study represents an attempt to understand how natural and human factors have influenced the formation and development of surface features within the basin.The study relied on satellite imagery, Digital Elevation Models (DEM), and both historical and contemporary topographic maps to compare changes in geomorphological characteristics such as drainage networks, erosion patterns, land use transformations, and vegetation cover changes. Spatial and statistical analysis tools within the GIS environment were used to identify areas of change and interpret their causes.The results revealed significant changes in the valley network and surface drainage over recent decades, due to human activities such as agriculture and grazing, as well as climate changes that affected rainfall amounts and surface runoff patterns. The study also showed an expansion in erosion-prone areas and a decline in some aspects of the natural vegetation cover.The research concludes that GIS is an effective tool for accurately monitoring and analyzing geomorphological changes and aids in developing future strategies for natural resource management and environmental planning in arid and semi-arid regions like the Hamad Al-Tajat Valley.